Antibacterial activity and mechanism of naphthoquine phosphate against ceftazidime-resistant Acinetobacter baumannii via cell membrane disruption and ROS induction - Yuan, Yongtian; Zhao, Liangliang; Bei, Zhuchun; Wang, Baogang; Zhang, Dongna; Xu, Likun; Liu, Jiahui; Lv, Meng; Xu, Qin; Song, Yabin (Frontiers in Microbiology, 2025)
IntroductionDrug-resistant bacteria, particularly Acinetobacter baumannii, present a significant threat to global public health, highlighting the urgent need for novel antibacterial therapies. Drug repurposing has emerged as a promising strategy to accelerate therapeutic development by identifying new applications for existing pharmaceuticals. This study investigates the potential of naphthoquine phosphate (NQP), an antimalarial agent, as a broad-spectrum antibacterial candidate against the multidrug-resistant strain A. baumannii LAC-4.MethodsTo evaluate the antibacterial activity of NQP, we determined the minimum inhibitory concentration (MIC) against Acinetobacter baumannii LAC-4. Inhibition kinetics were analyzed to assess concentration-dependent effects. Membrane permeability assays were performed to examine NQP-induced changes in cell membrane integrity. Oxidative damage tests were conducted to investigate impacts on bacterial metabolic processes. Morphological changes in A. baumannii LAC-4 treated with NQP of MIC were observed using transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Additionally, transcriptome analysis was performed to identify disrupted physiological pathways associated with NQP exposure.Results and discussionNQP exhibited broad-spectrum antibacterial activity, with a MIC of 62.5 μg/mL against Acinetobacter baumannii LAC-4. Its inhibition kinetics curve confirmed a concentration-dependent inhibitory effect. Membrane permeability tests revealed that NQP disrupts cell membrane integrity, enhancing permeability—consistent with TEM/SEM observations showing significant structural damage in NQP-treated A. baumannii, including membrane rupture, cellular deformation, and cytoplasmic disorganization. Oxidative damage tests indicated NQP impacts bacterial metabolism, and transcriptome analysis further demonstrated that NQP disrupts multiple physiological pathways, primarily through enhanced membrane permeability and induced oxidative stress. These findings support NQP as a promising molecular scaffold for developing novel therapies against Acinetobacter baumannii infections, highlighting its potential in drug repurposing strategies for combating drug resistance.